Długosz and Kallimach on the Hungarian crown of Władysław III - Nikodem, Jarosław (Balcanica Posnaniensia. Acta et studia, 1997)
The article is devoted to an analysis of the way Władysław III’s rule in Hungary is presented in the two most important Polish sources of the fifteenth century: Jan Długosz’s Annals and Filippo Callimachus’s Historia de rege Vladislao. The author examines the historiographical value of both works and their political and propagandistic function. The aim of the study is to compare the two narratives and determine the degree of Callimachus’s dependence on Długosz’s account. This issue is of great importance for understanding the mechanisms by which historical memory of the Polish-Hungarian union was shaped. The author employs a comparative analysis of historiographical texts, taking into account their political, ideological, and literary context. The article demonstrates that Długosz presented the reign of Władysław III not only as a struggle in defense of Christianity, but also as a response to the anti-Polish propaganda of Aeneas Silvius Piccolomini. Callimachus adopted many elements of this narrative, but did so mainly through the mechanical use of information contained in the Annals. The author emphasizes that Historia de rege Vladislao cannot be regarded as an independent and fully reliable historical source. The results of the analysis indicate that Długosz’s work was a conscious ideological and political construction, whereas Callimachus’s text was a literary adaptation of an earlier chronicle narrative.